On education and training - Orteza, Evelina Miranda (1991)
This paper clarifies the differences and the relationship between education and training. It identifies the conditions that constitute the necessary meaning of "an educated" person: 1) possession of knowledge, 2) coherent pattern of thought and a wide cognitive perspective and 3) self-educating. The paper argues that it is logically possible for graduates of contemporary universities to be trained to do something and at the same time to be an educated person.
Keywords: Continuing education; Trainings